Pengaruh Penggunaan Model Pembelajaran Examples Non-Examples terhadap Hasil Belajar Menulis Teks Berita pada Siswa Kelas VIII SMPN 14 Kota Tangerang - Agus Sulaeman; Ariyana Ariyana (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
The objective of this research was to determine the effect of the use of examples non examples models in class VII students of Class VIII SMPN 14 Tangerang City the method used in this study was the quasi experimental method by pretest and posttest two groups. This type of experimental research method uses the Nonequivalent Control Group Design research design. Where the experimental class is treated and the control class is not treated. The Nonequivalent Control Group Design is almost the same as the pretest and postest control of the design group, only in this design the experimental and control groups are not randomly selected. Data collection techniques using tests. The data analysis technique starts from the normality test, homogeneous test, and continues the hypothesis test. There are differences in learning outcomes of writing news texts between students who were given examples non-examples learning models with students who were not given examples non-examples learning and evidenced by the results of hypothesis testing, namely the pretest in the control class and the Ho accepted H1 experiment were rejected, it can be concluded that tcount < ttable (0.41 <2.0021) then the pretest did not have a significant difference in learning outcomes, and the results of the posttest hypothesis on the control class and experimental class were H1 accepted Ho was rejected because thitung> t table = 3.03 > 2.0021, then it can be stated that the giving of posttest in the control class that did not get treatment and the experimental class to get treatment using the examples non-examples learning model showed a very significant difference in learning outcomes.